Monitoring child survival in 'real time' using routine health facility records: results from Malawi. Issue 10 (1st August 2013) - Amouzou, Agbessi; Kachaka, Willie; Banda, Benjamin; Chimzimu, Martina; Hill, Kenneth; Bryce, Jennifer
Abstract: Objectives: Few developing countries have the accurate civil registration systems needed to track progress in child survival. However, the health information systems in most of these countries do record facility births and deaths, at least in principle. We used data from two districts of Malawi to test a method for monitoring child mortality based on adjusting health facility records for incomplete coverage. Methods: Trained researchers collected reports of monthly births and deaths among children younger than 5 years from all health facilities in Balaka and Salima districts of Malawi in 2010–2011. We estimated the proportion of births and deaths occurring in health facilities, respectively, from the 2010 Demographic and Health Survey and a household mortality survey conducted between October 2011 and February 2012. We used these proportions to adjust the health facility data to estimate the actual numbers of births and deaths. The survey also provided 'gold‐standard' measures of under‐five mortality. Results: Annual under‐five mortality rates generated by adjusting health facility data were between 35% and 65% of those estimated by the gold‐standard survey in Balaka, and 46% and 50% in Salima for four overlapping 12‐month periods in 2010–2011. The ratios of adjusted health facility rates to gold‐standard rates increased sharply over the four periods in Balaka, but remained relatively stable in Salima. Conclusions: Even in Malawi, where high proportions of births and deaths occur in health facilities compared with other countries in sub‐Saharan Africa, routine Health Management Information Systems data on births and deaths cannot be used at present to estimate annual trends in under‐five mortality.